Effects of Mediterranean Diet or Mindfulness-Based Stress Reduction on Prevention of Small-for-Gestational Age Birth Weights in Newborns Born to At-Risk Pregnant Individuals: The IMPACT BCN Randomized Clinical Trial. Issue 6 (June 2022) - Crovetto, Francesca; Crispi, Fàtima; Casas, Rosa; Martín-Asuero, Andrés; Borràs, Roger; Vieta, Eduard; Estruch, Ramon; Gratacós, Eduard
Abstract : (Abstracted from JAMA 2021;326:2150–2160) Babies with birth weights below the 10th percentile, or small for gestational age infants (SGA), are at risk of poor neurodevelopment or perinatal mortality. Although there is currently no effective prevention therapy for SGA, this study aimed to evaluate the value of structured lifestyle interventions such as a Mediterranean diet or stress reduction therapy in terms of reducing incidence of birth weight <10th percentile and adverse pregnancy outcomes.